Mexico : Reaching the Poor with Basic Health Services - Marquez, Patricio; de Geyndt, Willy (World Bank, Washington, DC, 2012)
In the mid-1990s, many Mexicans lived in poverty without adequate access to health and social services. Of a total population of 84 million, 25 percent were considered poor and 16 percent, extremely poor. Urban areas had health indicators similar to OECD countries, with an increasing burden of non-communicable diseases and injuries, while many people in rural areas and the southern states still suffered from common infectious diseases and malnutrition. Life expectancy in rural areas was 55 versus 71 in urban areas and 53 among the poor. The Mexican government realized that inequitable access to basic health care for poor and indigenous people hampered economic development, jeopardized investments in basic education and deprived citizens of their constitutional right to attain good health. So it devised a strategy to reduce inequities, improve health care, and modernize the Federal Health Secretariat (SSA). A 1994 presidential decree created a Health Cabinet (Gabinete de Salud) headed by the President with representatives from social security, finance and other social sector entities, to guide the SSA restructuring, promote coordination among sectors, and oversee the decentralization of health services.